The Analysis of Tupperware Marketing Strategy: Consumer Behavior Approach - Humaira, Putri; Handayati, Yuanita (Journal of Business and Management, 2016)
Abstract. Consumers have needs and wants that need to be fulfilled, where the needs and wants influenced by the internal or external factors. The company who able to provide the product that can fulfill the consumer demand will win the competition in the market. The company should able to build an effective marketing strategy that suitable with their market segments.Â  One of products that have a stiff competition is plastic container for food and beverage. There are big companies that sell this kind of products. Thus, Tupperware as the leading company of plastic container product needs to know the consumer behavior of plastic product in order to win the competition and can not defeat easily by the competitor. This research presented a data about Tupperware company, specifically about marketing strategy of Tupperware. This research will observe one of distributor Tupperware that located in Padang area, named PT Bumi Padang Gempita since this company faces the declining of sales growth percentage. Therefore, this research focused on the checking the relevancy between marketing strategy of Tupperware with the consumer behavior of plastic container product in Padang. The marketing strategy will be derived from the depth-interview with the distributor of Tupperware and the employee. While the consumer behavior will be derived from the questionnaire that includes demography of respondent, marketing mix, and decision-making process of consumer. After that, the consumer behavior will be analyzed using the K-means of cluster analysis from SPSS Software. Cluster analysis is used to categorize the consumer of plastic product based on the tendency of consumer in purchasing plastic container product. The researchâ€™s result shows that consumer of plastic container product divided into four clusters. Each clusters indicates the different characteristics of consumer in purchasing plastic product. In addition, the marketing strategy of Tupperware is relevant with the cluster number one and number three, which comprise of the durability, quality, function, material of product and also the promotion.Keywords: consumer behavior, marketing strategy, K-Means cluster analysis, Plastic container product, Tupperware.